THE ROLE OF PLATELET-RICH FIBRIN FACILITATES THE HEALING OF GASTROCNEMIUS MUSCLE DEFECT: A PRELIMINARY STUDY ON ANIMAL MODEL - Dwikora Novembri Utomo; Kukuh Dwiputra Hernugrahanto (Journal Orthopaedi and Traumatology Surabaya, 2018)
Background: Scar formation has been a classical issue in the healing of skeletal muscle defect which will results in decrease of strength and function. Platelet-rich plasma (PRP) has been studied to enhance the healing of muscle defect. The disadvantages of it include the risk of immunologic reaction, time-consuming preparation, and lack of scaffold element. Platelet-rich fibrin (PRF) is a new generation of platelet concentrate that provides good source of growth factors and scaffold element necessary for the healing. This study is to provide a fondation of PRF preparation and implantation for the healing of experimental defect of gastrocnemius muscle in an animal model.Purpose: The goal is to provide a fondation of PRF preparation and implantation for the healing of experimental defect of gastrocnemius muscle in an animal model.Methods: Animal Care and Use Committee, Airlangga University approved the study. Twenty New Zealand white rabbits were divided into two groups. In control group, a defect was created in the right gastrocnemius and no implantation was done. In study group, similar defect was created with implantation of PRF. Two and four weeks after surgery, the defect was examined immunohistochemically for the expression of Pax7 protein.Results: The implanted group showed higher IRS score in two and four weeks compared to the control group.Conclusion: The use of PRF facilitates the healing of muscle injury. This study will be used as a fondation for further study on PRF.